Characterization and control of oocyte large-scale chromatin configuration in different cattle breeds - Silva Soares, Ana Caroline [UNESP]; Sakoda, Jhessica Naomi [UNESP]; Gama, Isabela Lima [UNESP]; Bayeux, Bernardo Marcozzi; Lodde, Valentina; Luciano, Alberto Maria; Buratini, Jose [UNESP] (Elsevier B.V., 2020)
Differences in reproductive physiology between cattle breeds may help to explain distinct responses to assisted reproductive techniques and to define breed-specific protocols with improved efficiency. Germinal vesicle (GV) stage oocytes are characterized by increasing levels of chromatin compaction enclosed within the nucleus (graded from GV0 to GV3), associated with different developmental competence. The first objective of this study was to characterize chromatin configuration of GV stage oocytes recovered by OPU at random days of the estrous cycle from Nelore (Bos indices) and Holstein (Bos taurus) cows. In Nelore 90% of the oocytes presented advanced stages of chromatin compaction associated with higher developmental competence (GV2 and GV3), while in Holstein, only 65% of the oocytes were at these stages. Then, aiming to obtain a more homogeneous population of oocytes in Holstein, we tested two synchronization protocols combining aspiration of all visible follicles at a random day (day 0), two IM injections of FSH 12 h apart on day 2, and OPU on day 4 (OPU/D4) or 5 (OPU/D5). The protocol OPU/D4 provided around 45% of the oocytes with low chromatin compaction (GV1), while the protocol OPU/D5 provided 70% of the oocytes at GV2 and 20% at GV3. Finally, we assessed the effects of a culture system known to prevent meiotic resumption on chromatin configuration of the GV2 enriched oocyte population obtained with the protocol OPU/D5. After 9 h of culture most oocytes transited from GV2 to GV3, with 90% of the oocytes at GV3 stage. This study demonstrates differences between Nelore and Holstein cows regarding patterns of chromatin configuration that may account for their different performance in IVM/IVF. In addition, it provides novel references for the design of protocols aiming to regulate oocyte quality before IVM for the optimization of IVF outcomes. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: OPU; Follicle synchronization; Germinal vesicle; Pre-maturation; NPPC; Estradiol; Progesterone; Testosterone